Forced Migration in Canada - Clark-Kazak, Christina (Université d'Ottawa | University of Ottawa, 2024)
Forced Migration in Canada is intended to be a comprehensive repository of teaching and learning resources related to displacement to, and in, Canada, from colonization and slavery, to trafficking, statelessness and refugee protection and resettlement. Each section offers a compilation of multimedia resources to introduce students, researchers and the general public to the key issues.
Keywords: Migration; Immigration; Displacement; Refugees; Open educational resource (OER)